2010
DOI: 10.1371/journal.pgen.1001136
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variation Controls the Architecture of Somatic Alterations in Tumors

Abstract: Studies have suggested that somatic events in tumors can depend on an individual's constitutional genotype. We used squamous cell carcinomas (SCC) of the skin, which arise in high multiplicity in organ transplant recipients, as a model to compare the pattern of somatic alterations within and across individuals. Specifically, we performed array comparative genomic hybridization on 104 tumors from 25 unrelated individuals who each had three or more independently arisen SCCs and compared the profiles occurring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…The relationship between frequency of genomic alterations and genetic background has also been observed in other murine models of cancer (15). Data from analyses of mouse (16) and human (17) squamous cell carcinomas also support the notion of genetic background affecting the pattern of somatic alterations in tumors. The potential interactions between germline variants and somatic alterations could influence not only cancer susceptibility (18), but can also affect tumor progression and disease prognosis.…”
Section: Discussionmentioning
confidence: 61%
“…The relationship between frequency of genomic alterations and genetic background has also been observed in other murine models of cancer (15). Data from analyses of mouse (16) and human (17) squamous cell carcinomas also support the notion of genetic background affecting the pattern of somatic alterations in tumors. The potential interactions between germline variants and somatic alterations could influence not only cancer susceptibility (18), but can also affect tumor progression and disease prognosis.…”
Section: Discussionmentioning
confidence: 61%
“…Although C57BL/6 is highly resistant to DMBA/TPA skin carcinogenesis and developed only a modest number of papillomas in WT mice (~16 tumors/mouse), it was found that Hras KO/KO animals developed significantly fewer tumors (~3 tumors/mouse) 17 . Because genetic background can affect tumor development as well as pattern of genetic alterations in tumors 10, 18-20 , we backcrossed the Hras KO allele into the FVB/N background for more than 15 generations. FVB/N mice are highly susceptible to the development of epithelial tumors, and particularly skin tumors 21 .…”
Section: Resultsmentioning
confidence: 99%
“…A different spectrum of somatic mutations might also be caused by the distinct genetic backgrounds of Asian and Western populations, as germline variations have been shown to influence the somatic alterations that occur in tumors. 57 Moreover, exposure to certain etiological agents such as infectious diseases, including oncogenic viruses, or dietary habits could result on the usage of different oncogenic pathways. Indeed, 45% of the Chinese patients screened by exome sequencing presented some types of chronic infection at diagnosis including hepatitis B virus (23%), EpsteinBarr virus (10%), Helicobacter pylori (10%), and tuberculosis (10%), most of which have been shown to be highly prevalent in Chinese populations.…”
Section: Discussionmentioning
confidence: 99%